2014
DOI: 10.2422/2036-2145.201106_006
|View full text |Cite
|
Sign up to set email alerts
|

The integrability of negative powers of the soution to the Saint Venant problem

Abstract: We initiate the study of the finiteness condition Z u(x) dx  C(, ) < +1where ✓ R n is an open set and u is the solution of the Saint Venant problem 1u = 1 in , u = 0 on @. The central issue which we address is that of determining the range of values of the parameter > 0 for which the aforementioned condition holds under various hypotheses on the smoothness of and demands on the nature of the constant C(, ). Classes of domains for which our analysis applies include bounded piecewise C 1 domains in R n , n 2, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…This equation has several different names: the torsion function [2] or the Saint Venant problem [8] in the theory of elasticity, the landscape function [10] in the theory of localization of eigenfunctions of elliptic operators and half of the expected lifetime of Brownian motion before exiting the domain Ω in probability theory. It is also one of the elliptic 'benchmark' PDEs which are usually the first testcase for new results [3,16,23].…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…This equation has several different names: the torsion function [2] or the Saint Venant problem [8] in the theory of elasticity, the landscape function [10] in the theory of localization of eigenfunctions of elliptic operators and half of the expected lifetime of Brownian motion before exiting the domain Ω in probability theory. It is also one of the elliptic 'benchmark' PDEs which are usually the first testcase for new results [3,16,23].…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…and use this function θ instead of η in the construction of the operator T . We briefly discuss how such a function θ can indeed be constructed: In [CMMR14] it was shown that for a bounded, open set Ω, whose boundary ∂Ω has zero Lebesgue measure and upper Minkowski dimension strictly less then N − α, for some 0 < α < N , it holds that (5.5)…”
Section: Approximation Results In L P Spacesmentioning
confidence: 99%
“…Revisiting Carbery's estimate. A natural question is whether it is possible to weaken the assumptions in Carbery's estimate (this was also discussed by Carbery-Maz'ya-Mitrea-Rule [7] by very different means). We note that, with the inequality of arithmetic and geometric mean, we obtain…”
Section: Resultsmentioning
confidence: 99%